2007
DOI: 10.1093/ndt/gfm572
|View full text |Cite
|
Sign up to set email alerts
|

The role of renal biopsy in women with kidney disease identified in pregnancy

Abstract: Diagnosis and follow-up of renal disease diagnosed in pregnancy is important as progressive disease occurs in this group. Routine antenatal screening provides a useful diagnostic opportunity to detect asymptomatic renal disease. In a selected sub-group, renal biopsy during pregnancy can be helpful in initiation of correct treatment and allowing progression of pregnancy to fetal viability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 19 publications
0
36
0
4
Order By: Relevance
“…The risks and benefits of biopsy versus delivery should be considered with the obstetrical and neonatal providers. Although early studies reported high complication rates, including gross hematuria in 16.7% and perirenal hematoma in 4.4% (61), more recent series report similar complication rates to nonpregnant women (62,63).…”
Section: Antepartum Managementmentioning
confidence: 96%
“…The risks and benefits of biopsy versus delivery should be considered with the obstetrical and neonatal providers. Although early studies reported high complication rates, including gross hematuria in 16.7% and perirenal hematoma in 4.4% (61), more recent series report similar complication rates to nonpregnant women (62,63).…”
Section: Antepartum Managementmentioning
confidence: 96%
“…Day et al [20] showed that pregnancy itself does not increase the risk associated with a renal biopsy. In contrast to that, other investigators reported a significantly higher risk of complications for kidney biopsies in pregnancy, with a peak at around the 25 th gestational week [21] .…”
Section: Proteinuria In Pregnancymentioning
confidence: 99%
“…Publicaciones posteriores muestran una disminución franca de las complicaciones. En la última década queremos destacar dos por su mayor casuística: una revisión retrospectiva (1990-1999), publicada por Chen et al (n = 15, mediana de edad 28 años), y otra 14,3 . Llama la atención el número de casos comunicados que no supera los 15 por década.…”
Section: Discussionunclassified
“…La otra desarrolló una falla renal aguda de causa incierta. Ambas reunían las condiciones que se estiman necesarias para una adecuada relación riesgo/beneficio de la biopsia renal 3 .…”
Section: Discussionunclassified
See 1 more Smart Citation